2007
DOI: 10.3200/tsss.98.5.180-184
|View full text |Cite
|
Sign up to set email alerts
|

Strategies for Teaching Social Studies to English-Language Learners at the Elementary Level

Abstract: Learning social studies curriculum can present challenges for English-language learners (ELLs). The language used to present concepts is often decontextualized and abstract, making it difficult for these students to understand the content and have successful learning experiences. In this article, the authors describe strategies elementary teachers can use to make social studies content more comprehensible to ELLs and engage them to become active participants in their learning. They discuss three strategies in-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 1 publication
0
10
0
2
Order By: Relevance
“…A group of articles provides teaching suggestions for history (Brown, 2007; Egbert & Simich-Dudgeon, 2001; Field, Wilhelm, Nickell, Culligan, & Sparks, 2001; Olmedo, 1993; Pappamihiel, Lake, & Rice, 2005; Salinas, Fránquiz, & Guberman, 2006; Seda, Liguori, & Seda, 1999; Szpara & Ahmad, 2007; Urdanivia-English, 2001; Weisman & Hansen, 2007). Most of these articles describe the authors’ experiences as teachers or researchers, but they do not refer to research in which the effectiveness of the recommended techniques was measured through assessment or focused observation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A group of articles provides teaching suggestions for history (Brown, 2007; Egbert & Simich-Dudgeon, 2001; Field, Wilhelm, Nickell, Culligan, & Sparks, 2001; Olmedo, 1993; Pappamihiel, Lake, & Rice, 2005; Salinas, Fránquiz, & Guberman, 2006; Seda, Liguori, & Seda, 1999; Szpara & Ahmad, 2007; Urdanivia-English, 2001; Weisman & Hansen, 2007). Most of these articles describe the authors’ experiences as teachers or researchers, but they do not refer to research in which the effectiveness of the recommended techniques was measured through assessment or focused observation.…”
Section: Resultsmentioning
confidence: 99%
“…In these articles, linguistic, cognitive, and sociocultural concerns are all addressed. Linguistic issues are primarily oriented toward vocabulary teaching and learning (Pappamihiel et al, 2005; Salinas et al, 2006; Weisman & Hansen, 2007). Cognitive issues also address vocabulary knowledge; teachers can, for example, assist students to utilize strategies such as recognizing cognates or word roots when reading (Field et al, 2001; Szpara & Ahmad, 2007).…”
Section: Resultsmentioning
confidence: 99%
“…Their study reported that challenges included: the emergent bilinguals' lack of background knowledge and -lack of time, resources, and support‖ (Cho & Reich, 2008, p. 237). Moreover, Weisman and Hansen (2007) state some of the challenges emergent bilingual students face are due to the various cultures, languages, and prior educational experiences. Additionally, -Social studies may be the most difficult subject for ELLs‖ because it depends tremendously on language skills (Weisman & International Journal on Social and Education Sciences (IJonSES) 199 Hansen, 2007, p. 181).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Amerikanska studier om texter som elever läser i SO har visat att texterna ofta har tekniskt och abstrakt ordförråd, otydlig berättarstruktur, komplex meningsstruktur, en tendens att inte kopplas till konkreta sammanhang och förutsätter bakgrundskunskaper (se exempelvis Lee Brown, 2007;Weisman & Hansen, 2007;Szpara & Ahmad, 2007). Vidare är många texter informationstunga vilket kan skapa svårigheter i elevers läsande (Lee Brown, 2007;Weisman & Hansen, 2007). I ett svenskt sammanhang finns dock få studier om SO-texter, och de studier som finns behandlar inte texter i samhällskunskap utan i andra SO-ämnen så som geografi (t.ex.…”
Section: Forskningsbakgrundunclassified